Acre and Its falls
1 online resource.
Keywords: In the crusader period Acre was in many ways a remarkable place, but the most striking thing about its history is the number of times it fell to enemies. The present volume Acre and Its Falls is unusual in that it analyses a wide range of aspects of the history of Acre across the crusader period, combining political, military and cultural history, with a notable emphasis on the memory of the city in Europe. This may have been a city famous for its falls, but most certainly not for them alone. Contributors are Adrian J. Boas, Charles W. Connell, Paul F. Crawford, Susan B. Edgington, Marie-Luise Favreau-Lilie, John France, Anna Gilmour-Bryson, John D. Hosler, Georg Philipp Melloni, Janus Møller Jensen, J. Rubin, and Iris Shagrir.